FORGIVENESS AS A PREDICTOR OF GRATITUDE: ANALYSING RELATIONSHIPS AMONG SELF-COMPASSION, FORGIVENESS, AND GRATITUDE IN DELHI NCR - Limaye, Ritika; Chhabra, Lavanya; Singh, Suruchi; Rani, Manju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study examines the relationships between gratitude, forgiveness, and self-compassion among individuals residing in Delhi NCR. Settings and Design: A correlational research design was employed, with data collected from 156 participants using standardized psychological measures. Material and Methods: The study utilized the Gratitude Questionnaire (GQ-6), Rye’s Forgiveness Scale, and Neff’s Self-Compassion Scale to assess these constructs. Pearson’s correlation analysis and regression analysis were conducted using IBM SPSS 26. Results: Pearson’s correlation analysis revealed a significant positive relationship between forgiveness and gratitude (r = 0.280, p < 0.01), suggesting that individuals with higher levels of forgiveness also experience greater gratitude. Self-compassion demonstrated weak negative correlations with both gratitude (r = -0.093, p = 0.250) and forgiveness (r = -0.118, p = 0.141), though these relationships were not statistically significant. Regression analysis indicated that forgiveness significantly predicts gratitude, accounting for 7.8% of its variance (R² = 0.078, p < 0.001). Conclusion: The findings emphasize the crucial role of forgiveness in nurturing gratitude, while the relationship between self-compassion and these constructs requires further exploration. This study contributes to the understanding of emotional well-being by highlighting the consistent nature of forgiveness and gratitude, highlighting their significance in promoting positive interpersonal relationships and psychological resilience.